Steatotic Liver Disease: New Nomenclature and Its Localization in the Russian Federation - K. L. Raikhelson; M. V. Maevskaya; M. S. Zharkova; V. R. Grechishnikova; S. V. Okovityi; T. A. Deeva; N. V. Marchenko; M. К. Prashnova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: localization of the new nomenclature of steatotic liver disease in Russian clinical practice.Key points. In 2023, international consensus decided to introduce a new nomenclature for steatotic liver disease. The article discusses the reasons for the change in nomenclature and the new terms adopted: steatotic liver disease, metabolic dysfunction-associated steatotic liver disease, metabolic dysfunction and alcohol associated steatotic liver disease. Adapting new terms to Russian healthcare poses a certain problem. The results of voting by Russian doctors on the introduction of new terms and their optimal translation are presented. A comparison of existing classifiers with new terms was carried out and the formulation of diagnoses was discussed taking into account the new nomenclature.Conclusions. Adaptation and implementation of new nomenclature into clinical practice is an important and complex task, in which it is necessary to maintain a balance between a progressive concept and the interests of practical healthcare.